2008
DOI: 10.4064/ap94-3-6
|View full text |Cite
|
Sign up to set email alerts
|

Subextension of plurisubharmonic functions without increasing the total Monge–Ampère mass

Abstract: Abstract. We prove that subextension of certain plurisubharmonic functions is always possible without increasing the total Monge-Ampère mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…[41,75] for further applications). This chapter is mainly based on the joint work of the author and Lisa Hed in [47]. Here we shall prove the following theorem.…”
Section: Subextensionmentioning
confidence: 92%
“…[41,75] for further applications). This chapter is mainly based on the joint work of the author and Lisa Hed in [47]. Here we shall prove the following theorem.…”
Section: Subextensionmentioning
confidence: 92%
“…We have (dd c w) n = {u=−∞}∩ (dd c u) n < +∞ then Proposition 2.2 in [6] implies that w ∈ F( , f ). Put…”
Section: Proposition 25 Let Be a Bounded Hyperconvex Domain In C N Amentioning
confidence: 92%
“…Namely, in 2008, in [6], the authors showed that if and are two bounded hyperconvex domains such that ⊂ ⊂ C n , n ≥ 1 and…”
Section: Introductionmentioning
confidence: 99%